CRBF: Cross-Referencing Bloom-Filter-Based Data Integrity Verification Framework for Object-Based Big Data Transfer Systems - Kasu, Preethika; Hamandawana, Prince; Chung, Tae Sun (Applied Sciences (Switzerland), 2023)
Various components are involved in the end-to-end path of data transfer. Protecting data integrity from failures in these intermediate components is a key feature of big data transfer tools. Although most of these components provide some degree of data integrity, they are either too expensive or inefficient in recovering corrupted data. This problem highlights the need for application-level end-to-end integrity verification during data transfer. However, the computational, memory, and storage overhead of big data transfer tools can be a significant bottleneck for ensuring data integrity due to the large size of the data. This paper proposes a novel framework for data integrity verification in big data transfer systems using a cross-referencing Bloom filter. This framework has three advantages over state-of-the-art data integrity techniques: lower computation and memory overhead and zero false-positive errors for a limited number of elements. This study evaluates the computation, memory, recovery time, and false-positive overhead for the proposed framework and compares them with state-of-the-art solutions. The evaluation results indicate that the proposed framework is efficient in detecting and recovering from integrity errors while eliminating false positives in the Bloom filter data structure. In addition, we observe negligible computation, memory, and recovery overheads for all workloads.
Keywords: Bloom filters; data integrity; distributed systems; false-positive errors; high-performance computing; probabilistic structures